Immunomodulatory effect of hepatitis B virus (HBV) antigens and MRSA antigens on immune response - Entidhar A. Hadi; Mohammad Abd-Kadhum Al-Saadi; Kaiser N. Madlum (Medical Journal of Babylon)
Abstract Background: Methicillin-resistant Staphylococcus aureus is one of the most common human invaders and causes different types of illness worldwide. Objectives: This study aimed to illustrate the immune response of purified human peripheral blood mononuclear cells against somatic antigens of methicillin-resistant S. aureus (MRSA) and to study the immunomodulatory effect of hepatitis B virus (HBV) antigens on this immune response. Materials and Methods: A case–control study was applied on 75 peripheral blood mononuclear cells (PBMCs) samples. This work involved five experimental groups, each group involved 15 samples. Group I involves separated PBMCs (1 × 106 cells/mL) alone as a control; group II involves PBMCs stimulated with killed somatic MRSA antigen; group III of PBMCs were stimulated with HBV vaccine only; group IV involves PBMCs pretreated with HBV vaccine for 48 h, then with killed somatic MRSA antigen; and group V involves PBMCs stimulated with mixed of killed somatic MRSA antigen and HBV vaccine. The immune response against MRSA somatic antigens was assessed by measurement of interferon-γ, interleukin-4, and interleukin-5 by enzyme-linked immunosorbent assay technique. Results: The results indicated a significant increase (P < 0.05) in the mean value of IFN-γ in group II (125.9995 pg/mL) and III group (133.6504 pg/mL) and group IV (132.0271 pg/mL) as compared with control (group I) (49.6203 pg/mL). Also, the results showed no significant differences between control group I and group V (49.6203 and 9.6087 pg/mL). IL-4 and IL-5 concentration results revealed a significant increase in all treated groups as compared with control untreated group I. Conclusion: Immune response represented by regulatory cytokines against MRSA is significantly induced by somatic antigens.